2019
DOI: 10.5946/ce.2018.046
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Findings in Children with Isolated Lower Gastrointestinal Bleeding

Abstract: Background/Aims Colorectal polyps are a common cause of lower gastrointestinal bleeding in children. Our aim was to study the causes of isolated lower gastrointestinal bleeding and to analyze the characteristics of the colorectal polyps found in our cohort. Methods We retrospectively reviewed colonoscopic procedures performed between 2007 and 2015. Children with isolated lower gastrointestinal bleeding were included in the study. Results A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…Chair of Pediatrics, NESMOS Department, Sapienza University of Rome, Sant'Andrea University Hospital, Via di Grottarossa 1035-1039, 00189 Rome, Italy. 2 Pediatric Radiology Unit, Santobono-Pausilipon Children Hospital, Naples, Italy. 3 Department of Woman, Child and General and Specialistic Surgery, University of Campania "Luigi Vanvitelli", Naples, Italy.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chair of Pediatrics, NESMOS Department, Sapienza University of Rome, Sant'Andrea University Hospital, Via di Grottarossa 1035-1039, 00189 Rome, Italy. 2 Pediatric Radiology Unit, Santobono-Pausilipon Children Hospital, Naples, Italy. 3 Department of Woman, Child and General and Specialistic Surgery, University of Campania "Luigi Vanvitelli", Naples, Italy.…”
Section: Fundingmentioning
confidence: 99%
“…Colorectal polyps are reported in 6,1% of paediatric colonoscopies and in 12% of those performed for lower gastrointestinal bleeding. However, these lesions occur much more often than is clinically recognized because many of these polyps simply outgrow their blood supply, become ischaemic, and autoamputate with moderate painless haematochezia [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Although some cases of lower gastrointestinal bleeding can be diagnosed clinically [2], diagnosis is challenging in children with lower gastrointestinal bleeding without other symptoms. Silbermintz et al [3] described the role of endoscopic examination for diagnosis in children with lower gastrointestinal bleeding without other symptoms. The most common cause of asymptomatic lower gastrointestinal bleeding in children is juvenile polyps [2,4]; therefore, suspected juvenile polyps in children serve as an indication for colonoscopy.…”
mentioning
confidence: 99%
“…A multicenter study investigating 13,115 children who underwent colonoscopy in the USA reported that polyps were detected in 6.1% of all children who underwent colonoscopy and in 12% of children with lower gastrointestinal bleeding [5]. A study by Silbermintz et al [3] excluded children with clinically suspected inflammatory bowel disease, those with previously diagnosed polyps, and those with familial adenomatous polyposis. Therefore, it is not possible to directly compare the prevalence of colon polyps with that reported in other studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation